Representation of Victorian Society in the Poetry of Mary Howitt. / Representación de la sociedad victoriana en la poesía de Mary Howitt. - KUMAR, TRIBHUWAN (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The paper discusses Mary Howitt’s position as a representative poet of the victorian age. There are various other poets such as Alfred Tennyson, Robert Browning, Elizabeth Browning, Charlotte Bronte, Matthew Arnold, Shelley, Wordsworth, and George Eliot who represented and portrayed the varied conditions of victorian life. There are logical analysis and development of the poems. Appropriate theoretical frameworks have been incorporated whenever required. Based on discussion and interpretation, the researcher concludes that Mary Howitt can be well considered to be one of the representative poets of the victorian age. She has successfully rendered the darker side of victorian life.RESUMEN El artículo analiza la posición de Mary Howitt como poetisa representativa de la época victoriana. Hay varios otros poetas como Alfred Tennyson, Robert Browning, Elizabeth Browning, Charlotte Bronte, Matthew Arnold, Shelley, Wordsworth y George Eliot que representaron y retrataron diversas condiciones de la vida victoriana. Hay análisis lógicos y desarrollo de los poemas. Se han incorporado marcos teóricos apropiados siempre que sea necesario. Basándose en la discusión y la interpretación, el investigador concluye que Mary Howitt puede ser considerada una de las poetisas representativas de la época victoriana. Ha interpretado con éxito el lado más oscuro de la vida victoriana.